Análise do gerenciamento de resíduos sólidos recicláveis no Campus do PICI da Universidade Federal do Ceará / Erandi Canafístula Araujo - Araujo, Erandi Canafístula (Universidade Federal Rural do Semi-Árido, 2019)
The Brazilian legislation approaches the responsibility of public authorities to combat the main environmental problems arising from the inadequate management of solid waste. It also determines that the separation of the recyclable waste discarded by the organs and entities of the public administration must be made at the generating source and its destination to the associations and cooperatives of the collectors of recyclable materials. In this context, the following question emerges: how does the university deal with recyclable waste with a view to environmental sustainability? The present research aims to analyze how the management of such residues occurs in the Pici Campus of the Federal University of Ceará underthe sustainable aspect. Specifically, it proposes to identify the main recyclable waste generated in said Campus; to realizea diagnosis of handling, segregation, collection, storage, transportation and final destination of recyclable waste; to determine the main environmental impacts of the recyclable waste generated in the Campus do Pici;to identify existing sustainable practices and to propose environmental management guidelines related to recyclable waste. Itis a qualitative research, using techniquessuch as interview, direct observation, documentary and bibliographic research. As a result, the main recyclable waste generated in the Campus was identified, with emphasis on white paper, the main waste produced. A diagnosis of handling, segregation, collection, storage, transportation and final destination of recyclable waste was also carried out. The main environmental impacts of the recyclable waste generated in the Pici Campus were also determined, such as the donation of recyclable material to associations and collectors' cooperatives. The sustainable practices already existing in the university were also identified, among them: the presence of a department for internal environmental managementandconstructions and reforms in the institution followingsustainable standards. In addition, guidelines were proposed to promote the improvement of environmental management in the area of recyclable waste, such as: promoting the inclusion of other areas of the university in the collection of recyclable materials and increase of programs of awareness with the academic community regarding conscious consumption and concern for the environment and public health
Keywords: Sustentabilidade; Resíduos Recicláveis; Campus do Pici/UFC; Sustainability; Recyclable Waste; Campus do Pici/UFC; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA